Socio-demographic Characteristics and Cognitive Function in Adults with Type 2 Diabetes Mellitus (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Diabetes is a very common disease all over the world nowadays. Cognitive function impairment is closely related with socio-demographic characteristics of the diabetic patients.Objective: To assess the association between sociodemographic characteristics and cognitive function in adult type 2 diabetic (T2DM) patients.Materials and Methods: This cross sectional study was conducted among purposively selected 210 adult T2DM patients from July 2018 to June 2019 in two tertiary level hospital of Dhaka city. Data were collected by face to face interview using pretested semi-structured questionnaire and review of check list.Results: Mean age of the patients was 50.5 ± SD 7.4 years with male dominance (61.5%). The mean age of onset of diabetes was 41.6 ± SD 6.9. Most of the patients had normal cognitive function (71.4%) and had a mean MMSE (mini mental state examination scale) score of 25.2± SD 2.3. Statistically significant association was revealed between impaired cognitive function with age, monthly income, education, occupation, number of family members and types of residents of the respondents (p